Louboutin vs. Amazon. One more litigation about the liability of digital platforms in the use of a trademark? Commentary on the ECJ ruling of 22 December of 2022, cases C-148/21and C-184/21 - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The aim of this paper is the analysis of the ECJ ruling of 22 of December of 2022. The question that is resolved in the ruling we analyze is whether the fact that a third party that uses Amazon as a means to advertise and market counterfeit products can imply that the platform itself is directly liable for said infringement. It must be kept in mind that this direct responsibility of the platform would only be possible if it is considered that the platform itself uses another’s trademark within the meaning of art. 9.2 letter a) of Regulation (EU) 2017/1001. The study of this matter is necessary because it im- plies a greater precision even we can consider a change in the case law of the ECJ on the direct trademark liability of platforms. Following this ruling, a platform can be considered to use a trademark if, based on the perception of the average user who uses the platform, a link can be established between the trademark and the platform due to aspects such as (1) the way in which the platform offers the products (ad ex. in a homogeneous manner without differentiating between its own products and those of its sellers) and (2) the complementary services that the platform itself offers to its sellers.
Keywords: ecommerce platform; trademark; primary liability; luxury